Electronic Libraries of the Student Scientific Society at University of Library Studies and Information Technologies - Denchev, Stoyan; Kumanova, Alexandra; Vasilev, Nikolay; Todorova, Tania (Bobcatsss, 2023)
The goal of this study is to substantiate the bibliometric and humanitarian dimensions of the rhizomatic structured information resources in the university electronic environment. A subject of this study is the system unity of the twelve electronic libraries created of the Student Scientific Society (SSS) at ULSIT, such as: Universalica (for the genesis of the world universal bibliography from ІІІ c. BC – ХХІ c. in 20 languages according the originals); Humanitariana (for the bibliographies of the authors of conceptions of the humanitarian knowledge in Bulg. Rus. and Eng.); Etymologica (for the linguistic diversity of the terms and notions in the biblio-info-noosphere in Bulg. Rus. and Eng.); Anthology (of the information code of Bulgarian literature, letters and spirituality: ІХ-ХХІ c.); Autobiobibliography (structuring of autobiobibliographies of the figures – architects of SSS at the University – among whom are students, doctoral students, young scientists), and the issue of their regionalizing and mapping. Through the rhizomatic methodology positioning from framing modulation (facts – primary documents – secondary documents – metasystems – philosophical pictures of relations among things) the idea of the historiographic unification of the information resources of the university information environment in the cognitive context of the informatics was achieved. The methodology of regionalizing and mapping was positioning as a prerequisite for the realization of the conceptual humanitarian dimensions of the resources, which are especially pressing for the postnonclassical paradigm of the knowledge in the contemporary science with their intrinsic prognostic of fixation of directions to establish connections between information realities. Rhizomatic structuring of the historiography of the electronic libraries was assessed as a corresponding to the unique bibliographic and historiographic scientific school of Bulgaria with international recognition related to the creative laboratories of Acad. N. Mihov, Prof. T. Borov, Acad. I. Duychev, Prof. V. Velchev, Prof. K. Kuev, Prof. B. Angelov, Acad. P. Dinekov. The creation for the purposes of the digitization historiographical resource - electronic libraries of the Student Scientific Society (SSS) at ULSIT, available at: http://sno.unibit.bg/ - has the mission to preserve the thin layer of the established relations among things, representing the focal goal of the reference-information resources.